SCREENING OF ANTIBIOTIC RESIDUES IN BROILER CHICKEN MEAT FROM TRADITIONAL MARKETS IN PURBOLINGGO SUBDISTRICT, EAST LAMPUNG REGENCY, LAMPUNG PROVINCE, INDONESIA - Diah Reni Asih; Dwi Subakti Prastiyo; Rohmatul Anwar; Miftahuddin Ahmad (Universitas Muhammadiyah Malang, 2026)
The use of antibiotics in broiler production may result in residue accumulation in edible tissues when withdrawal periods are not properly observed. This study aimed to detect residues of four antibiotic classes, namely tetracyclines, macrolides, aminoglycosides, and β-lactams, in broiler chicken meat marketed in Purbolinggo District, East Lampung Regency, Lampung Province, Indonesia. Samples were collected using purposive sampling from five broiler meat vendors at the traditional market of Purbolinggo District. Approximately 500 g of breast meat was obtained from each vendor, resulting in a total of five samples. Antibiotic residues were screened using a laboratory-based bioassay method by observing inhibition zone formation around paper discs containing meat extracts. The presence or absence of inhibition zones was used as an indicator of antibiotic residues. No residues of tetracyclines, macrolides, aminoglycosides, or β-lactams were detected in any of the analyzed samples. These findings indicate that residue levels, if present, were below the detection limit of the screening method employed. The absence of detectable residues may suggest compliance with recommended antibiotic use practices and withdrawal periods; however, these factors were not directly evaluated in this study. Further investigations involving larger sample sizes and quantitative analytical methods are recommended to provide a more comprehensive assessment of antibiotic residue occurrence in broiler meat.